Preparation of a Nylon-11 Precursor from Renewable Canola Oil - Spiccia, Nicolas Daniel; Border, Emily; Illesinghe, Jayamini; Jackson, William Roy; Robinson, Andrea Jane (Synthesis, 2013)
We report a multi-catalytic sequence to a valuable nylon-11 precursor, methyl 11-aminoundecanoate, which is prepared by a ruthenium-catalysed cross-metathesis and a highly regioselective palladium-catalysed amination–hydrogenation reaction, from canola oil, a renewable, natural vegetable oil feedstock.
Keywords: metathesis; hydrogenation; amination; catalysis; polymers; nylon-11; canola; renewable